94.8k views
2 votes
Given f(x) = –x + 6 write an equation for f(x + 3). f(x + 3) = Choose... x Choose... Choose... .

User Matjan
by
4.5k points

1 Answer

6 votes

Answer:

f(x + 3) = -x + 3

General Formulas and Concepts:

  • Order of Operations: BPEMDAS
  • Properties

Explanation:

Step 1: Define

f(x) = -x + 6

f(x + 3) is x = x + 3

Step 2: Find

  1. Substitute: f(x + 3) = -(x + 3) + 6
  2. Distribute -1: f(x + 3) = -x - 3 + 6
  3. Combine like terms: f(x + 3) = -x + 3
User RavindUwU
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.